Aplicação da técnica da valoração econômica de ações de requalificação do meio ambiente em área degradada - Barbisan, Ailson Oldair (2006)
All city is an ecological system, and like this, there are a living organism group, where the man is the predominant one, a physical environment above inside transformation, and a change working from material, energy and knowledge. In this context, the studied area is located: an irregular occupation in a private area, with 200 families living in precarious houses in a flood dangerous local, near Passo Fundo river, around Cruzeiro neighborhood area, and near from downtown Passo Fundo, RS. Environmental problems have increased rapidly during the last years like an indicator of sustainability, but it is difficult to evaluate the environmental damage of an urban intervention and how much it cost. After the studied area has been characterised it was applied the Contingent Valuation Method, with DAP methodology (willingness-to-pay) to economic valuation of urban and environmental intervention. Three different groups of people were questioned, the first group living up to 200 m far from the studied area, the second up to 400 m and the third group more than 400 m distant. Cultural, social, economic and urban indicators as well as environmental impacts were studied to evaluate the people willingness to pay for different urban intervention and environmental resource recovery. At the same time, intend to suggest possible public urban management policies whereas the used method and results proved workable application considering different environmental aspects, mainly economic valuation of environmental damage